Abscessing Infection by Streptococcus mitis Mimicking Metastatic Lesions in a 5-Year-Old Girl With Nephroblastoma: A Case Report. Issue 7 (October 2018) - Imhof, Lara; Schrading, Simone; Braunschweig, Till; Steinau, Gerhard; Spillner, Jan Wilhelm; Puzik, Alexander; Lassay, Lisa; Kontny, Udo
Abstract : Streptococcus mitis is a common pathogen causing infections in oncological patients. However, cases of abscesses caused by Streptococcus mitis in oncological patients have not been reported so far. We report on 5-year-old child with nephroblastoma and pulmonary and hepatic metastases at diagnosis who went into complete remission undergoing chemotherapy and nephrectomy, and who developed new round lesions in liver and lungs under continuous chemotherapy suggestive of new metastases. Biopsy of the lesions revealed abscesses with detection of Streptococcus mitis . The child was successfully treated with antibiotics, finished chemotherapy per protocol and has been in complete remission for 14 months. Infectious lesions involving organs of typical metastatic dissemination can easily be misdiagnosed as metastases, especially in the absence of symptoms. Histologic proof of lesions suspicious of metastases is mandatory if it leads to a change of prognosis and therapy. Streptococcus mitis can be a causative organism of pulmonary and hepatic abscesses in oncological patients.